Ethical Perspectives of the Waste Land - Thottakara, Augustine (Journal of Dharma, 1999)
Thomas Sebastian Panachickavayalil, Ethical Perspectives of the Waste Land. A Study of T.S. Eliot's Poem in the Mutli-Religious Context of Today, Rome: Collegio San Lorenzo, 1999, pp. ix+260.